2021
DOI: 10.1017/s0007114521003524
|View full text |Cite
|
Sign up to set email alerts
|

Rare sugars: metabolic impacts and mechanisms of action: a scoping review

Abstract: Food manufacturers are under increasing pressure to limit the amount of free sugars in their products. Many have reformulated products to replace sucrose, glucose and fructose with alternative sweeteners, but some of these have been associated with additional health concerns. Rare sugars are “monosaccharides and their derivatives that hardly exist in nature”, and there is increasing evidence that they could have health benefits. This review aimed to scope the existing literature in order to identify the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Hereby, the research builds further upon the current knowledge on rare sugars and the existing in vitro models for testing cellular impact of nutrients. Currently, there is only a small number of rare sugars for which the metabolic health impact is known, as mentioned in recent reviews [ 35 , 36 ], and this is the first study to investigate metabolic health effects of the rare sugars D-Glc-α1,2-D-Gal, D-Glc-α1,2-D-Rib and D-Glc-α1,3-L-Ara. In addition, this study has used cellular energetics to obtain knowledge on cellular effects of disaccharides, whereas previous research has mainly focused on conventional monosaccharides [ 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hereby, the research builds further upon the current knowledge on rare sugars and the existing in vitro models for testing cellular impact of nutrients. Currently, there is only a small number of rare sugars for which the metabolic health impact is known, as mentioned in recent reviews [ 35 , 36 ], and this is the first study to investigate metabolic health effects of the rare sugars D-Glc-α1,2-D-Gal, D-Glc-α1,2-D-Rib and D-Glc-α1,3-L-Ara. In addition, this study has used cellular energetics to obtain knowledge on cellular effects of disaccharides, whereas previous research has mainly focused on conventional monosaccharides [ 25 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, major concerns have been expressed regarding the intake of metabolizable free sugars, which are usually replaced by artificial high-intensity sweeteners, such as aspartame, acesulfame potassium, saccharin, sucralose, and others, approved as food additives by the European Food Safety Authority (EFSA) and U.S. Food and Drug Administration (FDA) [8,9]. However, these alternative sweeteners are associated with unfavorable effects on health, such as glucose intolerance and failure to cause weight reduction [10]. Interestingly, naturally occurring rare sugars have recently appeared as a valuable alternative category of sweeteners.…”
Section: Introductionmentioning
confidence: 99%
“…Isomaltulose, an isomer of sucrose with glucose and fructose linked through an α-1,6 linkage instead of an α-1,2 linkage in sucrose, is digested at a slower rate than sucrose due to lower intestinal enzyme affinity, thus lowering postprandial glucose response and related inflammatory markers in patients with type 2 diabetes ( 21 ). Among other rare sugars, allulose is a C3 epimer of D-fructose and tagatose a stereoisomer of D-fructose ( 22 ). Due to their different conformations, they are either not metabolized (in the case of allulose) or not absorbed (in the case of tagatose), which results in a lower caloric content for both rare sugars.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond their lower caloric content, some studies have suggested they may have additional benefits by decreasing glucose-induced postprandial glycemia. The postulated mechanism may involve inhibition of α-glucosidase ( 22 ). The associations between total dietary carbohydrate intake and health-related outcomes have been intensively studied but remain debated.…”
Section: Introductionmentioning
confidence: 99%